IMPROVISATIONAL PRACTICES IN FOREIGN LANGUAGE TEACHING AS A MEANS OF DEVELOPING SPONTANEOUS SPOKEN LANGUAGE: INTEGRATION OF PSYCHOLINGUISTIC AND THEATER-PEDAGOGICAL APPROACHES - Galiullov Marat; Natalya Kashirina (International Journal of Literature and Language Studies, 2026)
Improvisational practices are examined as a tool for activating the mechanisms of spontaneous speech production in foreign language learning. Psycholinguistic models of speech production (the levels of conceptualisation, formulation and articulation) are compared with theatrical and pedagogical techniques aimed at reducing cognitive control and accelerating reaction times. Examples of tasks for German lessons at levels A2-B1 are provided. The absence of quantitative data in the sources consulted is noted; only verifiable propositions from the scientific tradition are used.